COVID-19 among Minority Children in Detroit, Michigan during the Early National Surge of the Pandemic - Jocelyn Y. Ang MD; Nirupama Kannikeswaran MD; Katherine Parker BS; Eric McGrath MD; Nahed Abdel-Haq MD; Harbir Arora MD; Jorge L. Lua MD; Ronald Thomas PhD; Hossein Salimnia PhD; Teena Chopra MD, MPH; Tommy Tran MPH; Basim Asmar MD (SAGE Publishing, 2021)
Background . The COVID-19 pandemic has shed light on communities of racial/ethnic minority groups in the US where long-standing health issues and structural inequities are now known to have resulted in increased risk for infection, severe illness, and death from the virus. The objective of our study was to describe demographic characteristics, clinical presentations, medical interventions and outcomes of pediatric patients with COVID-19 treated at Children's Hospital of Michigan (CHM), a tertiary care center in urban Detroit, an early hotspot during the initial surge of the SARS-CoV-2 pandemic. Methods. A retrospective chart review was performed of children ≤18 years of age who had polymerase chain reaction (RT-PCR) testing via NP swab or serum IgG antibody testing for SARS-CoV-2 during March 1, 2020-June 30, 2020. Results. Seventy-eight COVID-19 infected children were identified of whom 85.8% (67/78) were from minority populations (African American, Hispanic). Hospitalization rate was 82% (64/78). About 44% (34/78) had an associated comorbidity with asthma and obesity being most common. Although all ages were affected, infants <1 year of age had the highest hospitalization rate (19/64, 30%). In all disease severity categories, dichotomized non-whites had more severe disease by percentage within race/ethnicity than Whites, and also within percent disease severity ( P -value = .197). Overall, 37% of hospitalized patients required intensive care. Conclusions. Extremely high rates of COVID-19 hospitalization and requirement of ICU care were identified in our patient population. Further studies are needed to better understand the contributing factors to this health disparity in disadvantaged communities.